Constructivist Blended Learning Approach to Teaching English for Specific Purposes - Tarnopolsky, Oleg (De Gruyter, 2012)
This monograph analyzes an innovative approach to teaching English for Specific Purposes (ESP) in tertiary education. This "constructivist blended learning approach" is based on students "constructing" for themselves their own knowledge and professional communication skills in English by making extensive use of Internet sites in English, combining traditional in-class learning with in- and out-of-class learning through the Internet (blended learning). Dr. Tarnopolsky offers a thorough analysis of the principal forms of learning activities in English for this approach and suggests five principles underlying its practical implementation.